Barriers to healthcare: A brief overview of healthcare stigmas among Black and Hispanic/Latino patients. Issue 3 (May 2023) - Rodriguez, Thureiyya
Abstract : Stigmatization is a deep-rooted problem in US history that has affected generations of Black and Hispanic/Latino patients. By understanding these histories nurses can grow cultural humility in their practice. Abstract : Stigmatization is a deep-rooted problem in US history. By learning these histories, nurses can grow cultural humility in their practice.